Pyrolysis and Combustion Behavior of Flax Straw as Biomass: Evaluation of Kinetic, Thermodynamic Parameters, and Qualitative Analysis of Degradation Products - Bahareh Vafakish; Amin Babaei-Ghazvini; Mahmood Ebadian; Bishnu Acharya (Energies, 2023)
This study describes an investigation of the pyrolysis and combustion of flax straw as biofuel, focusing on the physicochemical properties and kinetic and thermodynamic parameters, and evaluates the type of degradation products using the thermogravimetry analysis–Fourier transform infrared spectroscopy (TGA-FTIR) technique. Pyrolysis and combustion processes were studied via thermogravimetric analysis at different heating rates of 5-10-15 and 20 °C min, one using three isoconversional methods and one using a model-fitting method. The activation energies, frequency factors, and thermodynamic parameters of flax straw biomass were investigated using different models. The obtained activation energy values for pyrolysis varied between 101.0 and 109.6 kJ mol−1 and for combustion were between 203.3 and 239.2 kJ mol−1. The frequency factors were determined to be 1.7 × 109 for pyrolysis and 1.5 × 1017 s−1 for combustion. The change in Gibbs free energy (ΔG) for the pyrolysis of flax straw was calculated to be 162.6 kJ mol−1, whereas for combustion it increased to 203.9 kJ mol−1. A notable contrast between the volatiles produced by pyrolysis and combustion is evident from the real-time analysis of the degradation products. Specifically, carboxylic acids, aromatics, alkanes, and alcohols are the principal degradation products during pyrolysis, while carbon dioxide is the primary component produced during combustion. These encouraging research outcomes regarding flax straw pyrolysis and combustion can broaden its application in bioenergy and biofuel, thus contributing significantly to it for resource recovery.